Moderating Effect of Organization Culture of The relationship of GIC to Organizational Performance - Endro Andayani; Erni Prasetiyani; Wati Aris Astuti (UPT Publikasi Ilmiah (Universitas Islam Bandung), 2025)
Abstract. The study aims to determine whether Green Intellectual Capital (GIC) has an effect on organizational performance with organizational culture as a moderating variable. Samples of 300 respondents with manager level in companies listed on the IDX and not listed. Data obtained through questionnaires, SEM PLS analysis was used with the Smart PLS statistical tool. The findings are that Green Human Capital (GHC) and Green Relation Capital (GRC) have an effect on organizational performance, but Green Structural Capital (GSC) doesn’t, and Organizational Culture as a moderating variable doesn’t strengthen the influence of GIC on organizational performance. The contribution:Provides existing knowledge in achieving higher levels of organizational performance in organizations of various industrial sectors by implementing various components of GIC. In the future, it will provide a better understanding of how GIC dimensions can contribute to organizations operating in a particular sector.